Trade and foreign direct investment-related impacts of Brexit - María C. Latorre; Zoryana Olekseyuk; Hidemichi Yonezawa (The World Economy, 2019)
We offer a general-equilibrium analysis of Brexit incorporating the state-of-the-art differences in productivity and firms' selection within manufacturing sectors à la Melitz (Econometrica, 2003, 71, 1695) and multinationals in services. Our results suggest that trade, output and average productivity diminish across most sectors in the UK and the Rest of the European Union (REU), as well as GDP, welfare, wages and capital remuneration. However, the UK loses more due to the missing preferential access to the huge EU market. Significant welfare losses along the extensive margin occur in the UK due to the lost imported varieties produced by highly productive European firms. These cannot be compensated by the new varieties of less productive domestic firms that enter the British market due to increased protectionism and reduced import competition. In addition, the emergence of barriers against multinationals, which is often ignored in previous studies, explains approximately one third of the negative effect in both the UK and REU. Furthermore, we show that the Brexit impact is about only half if we do not include both foreign direct investment barriers and Melitz structure. Thus, previous studies without these important model features would underestimate the Brexit impact significantly.
Keywords: 330; Melitz; monopolistic competition; Multinationals; trade in services